(untitled) (Web of Teachers: Inderscience Research, 2024)
The technological indicator of cotton fiber, chicken oil, and the effects of defoliants on nuclear output in questioning the growth and development of the S-8290 grain variety, which is being cared for in the weakly salted soils of the province of Anchorage.